2019
DOI: 10.1037/pspp0000216
|View full text |Cite
|
Sign up to set email alerts
|

The meaning of guilt: Reconciling the past to inform the future.

Abstract: Despite decades of empirical research, a deceptively simple question remains unanswered: Is guilt good? Whereas some researchers assert that routine experiences of guilt (i.e., “trait guilt”) are maladaptive and indicative of poor psychological adjustment, others assert trait guilt to be adaptive and indicative of a prosocial disposition. In the current research we outline the theoretical underpinnings of 2 of the most commonly employed measures of trait guilt: unsituated measures (e.g., the Personal Feelings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 94 publications
2
18
0
Order By: Relevance
“…Similar to other studies (Barr & Cacciatore, 2007; Di Sarno et al, 2019; Dorahy et al, 2013; Gambin & Sharp, 2018; D. H. Harder & Zalma, 1990; Rüsch et al, 2007; Tignor & Colvin, 2019), we also observed that the revised shame subscale had good internal consistency and could therefore be considered a reliable measure of the frequency of shame experiences in our sample. Our observed sample mean of 5.65 for the revised shame subscale appeared to be low given the possible range of scores (range = 0-18).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to other studies (Barr & Cacciatore, 2007; Di Sarno et al, 2019; Dorahy et al, 2013; Gambin & Sharp, 2018; D. H. Harder & Zalma, 1990; Rüsch et al, 2007; Tignor & Colvin, 2019), we also observed that the revised shame subscale had good internal consistency and could therefore be considered a reliable measure of the frequency of shame experiences in our sample. Our observed sample mean of 5.65 for the revised shame subscale appeared to be low given the possible range of scores (range = 0-18).…”
Section: Discussionsupporting
confidence: 89%
“…W. Harder et al, 1992; D. W. Harder & Greenwald, 1999; Tignor & Colvin, 2019) that used the PFQ-2 in its original English form. The lower levels of shame observed in our sample may indicate that the Spanish-translated adjectives included in the PFQ-2 shame subscale, which were developed and tested in English among undergraduate students, may not hold the same negative emotional magnitude (e.g., “self-consciousness”) or be as relatable (e.g., “childish”) to the experiences of shame among our sample of FSWs in Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this line of argumentation refers to contextualized forms of guilt, that is, the experience of guilt in response to transgressions as an adaptive, normative guilt response. Such contextualized guilt needs to be distinguished from trait guilt, a person's chronic disposition to experience guilt irrespective of context, which is maladaptive (Tignor, & Colvin, 2019). 2…”
Section: Mindfulness Shapes Affective and Behavioral Reactions To Enacted Incivilitymentioning
confidence: 99%
“…Shame as measured by the TOSCA has shown far less systematic associations with values than has guilt, but positive correlations with tradition and conformity and negative correlations with self-direction and power have been found ( Silfver et al, 2008 ; Helkama et al, 2018 ). Guilt is associated with prosocial behavior ( Tignor and Colvin, 2019 ).…”
Section: Introductionmentioning
confidence: 99%